Short‐term high‐fat diet exacerbates insulin resistance and glycolipid metabolism disorders in young obese men with hyperlipidemia, as determined by metabolomics analysis using ultra‐HPLC–quadrupole time‐of‐flight mass spectrometry - Feng, Rennan; Sun, Guozhang; Zhang, Yunbo; Sun, Qintong; Ju, Liyan; Sun, Changhao; Wang, Cheng (Journal of diabetes, 2019)
Background The prevalence of obesity is increasing rapidly worldwide, and dietary intake is strongly associated with obesity‐related chronic diseases. However, key metabolic perturbations in obese young men with hyperlipidemia after high‐fat diet (HFD) intervention are not yet clear, and remain to be determined. The aim of this study was to investigate the effects of a short‐term HFD on glycolipid metabolism, insulin resistance (IR), and urinary metabolomic profiling in young obese men with hyperlipidemia. Methods Sixty young men (19–25 years; 30 normal weight, 30 obese with hyperlipidemia) were enrolled in the study. Differences in metabolomic profiling of urine between normal‐weight and obese young men before and after 3 days intake of the HFD were investigated using ultra‐HPLC–quadrupole time‐of‐flight mass spectrometry. Results After the HFD intervention, total cholesterol (TC), low‐density lipoprotein cholesterol, fasting plasma glucose, insulin, and homeostasis model assessment of insulin resistance (HOMA‐IR) were significantly increased and high‐density lipoprotein cholesterol was significantly decreased in obese men, but only TC was significantly increased in normal‐weight subjects. Based on metabolic differences, normal‐weight and obese men, and obese men before and after the HFD intervention could be separated into distinct clusters. Seventeen major metabolites were identified that were associated with type 2 diabetes mellitus, glycolipid metabolism and IR; the changes in these metabolites suggest metabolic changes in young obese males after short‐term HFD intake. Conclusions The findings of this study may contribute to increased understanding of the early biological adaptations of obesity with hyperlipidemia to HFD for the early prevention and control of diabetes and IR. 摘要 背景 肥胖的患病率在世界范围迅速增加,  而饮食摄入与肥胖相关慢性疾病密切相关。然而,  在高脂饮食后,  肥胖高血脂年轻男性的关键代谢紊乱尚不清楚,  并有待确定。本研究旨在探讨短期高脂饮食对肥胖高血脂年轻男性糖脂代谢、胰岛素抵抗及尿代谢谱的影响。 方法 60例青年男性(年龄19‐25岁,  体重正常30例,  肥胖高血脂30例)参与本研究。采用超高效液相色谱‐四极杆飞行时间串联质谱检测,  分析正常体重和肥胖男性在高脂饮食前和3天后尿代谢谱的差异。 结果 高脂饮食干预后,  肥胖男性的总胆固醇、低密度脂蛋白胆固醇、空腹血糖、胰岛素、胰岛素抵抗稳态模型评估指数(HOMA‐IR)显著升高,  且高密度脂蛋白胆固醇显著降低,  而体重正常的男性只有总胆固醇显著升高。正常体重和肥胖男性以及高脂饮食干预前后的肥胖男性根据其代谢差异可以形成不同的分类。共鉴定出与2型糖尿病、糖脂代谢和胰岛素抵抗相关的17种主要代谢物,  这些代谢物的变化表明了短期摄入高脂饮食后肥胖年轻男性的代谢改变。 结论 本研究的发现可能有助于提高肥胖高血脂对高脂饮食的早期生物学适应性的认识,  进而早期预防和控制糖尿病及胰岛素抵抗。 Highlights Effects of a 3‐day high‐fat diet (HFD) on insulin resistance (IR) and glycolipid metabolism in young obese men with hyperlipidemia was evaluated, with changes in urinary metabolomics profiling after the HFD intervention determined using ultra‐HPLC–quadrupole time‐of‐flight mass spectrometry. Short‐term HFD exacerbates IR and glycolipid metabolism disorders, and 17 major metabolites were identified that were associated with type 2 diabetes mellitus, glycolipid metabolism and IR; changes in these metabolites suggest metabolic changes in young obese males after the HFD intervention. These findings may contribute to an increased understanding of the early biological adaptations of obesity with hyperlipidemia to HFD for early prevention and control of diabetes and IR.